"Conflict-free" socio-economic systems : perspectives and contradictions - Popkova, Elena G. (Emerald Publishing Limited, 2019)
"Conflict-free" Socio-Economic Systems: Perspectives and Contradictions analyses crisis as a component of the growth and development process of economic systems, and its role within the economic cycle.The scientific treatment of the role of crisis in the development of economic systems has traditionally been divided into two conceptual approaches. The first conceptual approach views crisis as a possibility to reconsider the trajectory of economic development of both the national systems and the global economic system overall. However, most scholars, politicians, and experts focus on the second conceptual approach, within which economic crisis is seen as a temporary failure in the work of a system which hinders the process of economic growth and development. This became a precondition for proclaiming a new course of development of the modern national and global economic system oriented at sustainability.This book provides a strong theoretical and methodological basis to sustainable development of economic systems, for researchers and scholars in the area of economic theory and sustainable economics. In locating the role of crisis within socio-economic systems, Popkova advocates the concept of a "conflict-free" system as the landmark of global economic development.
Includes index.
Keywords: Sustainable development.; Economics.; Business & Economics -- Development -- Economic Development.; elektronické knihy; electronic books